Crustal Structure of the Hikurangi Margin From SHIRE Seismic Data and the Relationship Between Forearc Structure and Shallow Megathrust Slip Behavior. Issue 2 (18th January 2022) - Bassett, Dan; Arnulf, Adrien; Henrys, Stuart; Barker, Dan; van Avendonk, Harm; Bangs, Nathan; Kodaira, Shuichi; Seebeck, Hannu; Wallace, Laura; Gase, Andrew; Luckie, Thomas; Jacobs, Katie; et al.
Abstract: Marine multichannel and wide‐angle seismic data constrain crustal structure along a 530 km margin‐parallel transect of the Hikurangi subduction zone. The subducting Hikurangi Plateau crust ( V P 5.0–7.4 km/s) is ∼1 km thicker (11 ± 1 km) and mantle velocities are ∼0.2 km/s higher ( V P 8.3–8.5 km/s) beneath south/central Hikurangi relative to north Hikurangi. In the overthrusting plate, an abrupt 0.5 km/s south‐to‐north reduction in forearc wavespeeds occurs in concert with a change in seismic reflection character. We analyze legacy seismic data to show that the forearc transition likely reflects lateral variability in the updip extent of the Torlesse Backstop. Furthermore, we map this unit along‐strike and note a broad correlation between the backstop and down‐dip extent of shallow slow‐slip. We propose that the geological architecture of the overthrusting plate contributes to spatial variability in the location of shallow frictional transitions along the Hikurangi margin, impacting both seismic and tsunami hazard. Plain Language Summary: Some subduction zones produce the largest earthquakes and tsunami on Earth, while others slip freely. To understand what factors impact subduction zone slip behavior, we analyze seismic data along a 530 km long transect spanning a transition from strong (south Hikurangi) to weak (central/north Hikurangi) interseismic locking. From south‐to‐north, we find that seismic wavespeeds in the overthrusting plate undergo an abrupt (∼10%) reduction, which coincides with a reduction in seismic reflectivity. We show that these changes likely reflect differences in the offshore (updip) extent of basement rocks within the forearc crust, which we map using seismic data. These maps also show that the offshore extent of basement rocks is broadly correlated with the maximum depth of shallow slow‐slip events. We propose that geological architecture of the overthrusting plate may contribute to spatial variability in megathrust slip‐behavior, impacting both seismic and tsunami hazard along the Hikurangi margin. Key Points: Coincident reductions in seismic wavespeeds and lower‐crustal reflectivity occur from south‐to‐north along the Hikurangi forearc Legacy seismic reflection data attribute the forearc transition to along‐strike differences in the updip extent of the Torlesse Backstop Shallow slow‐slip is focused updip of the backstop, suggesting it may impact the location of shallow frictional transitions at Hikurangi